(untitled) (The Pretoria Student Law Review, 2021)
In this article the author offers an analysis and critique of the positionality of Black Queer women within modern identity politics in order to unpack and demonstrate the ways in which their identity and the multiple forms of oppression and violence attached to these identities need an integrated and intersectional approach that extends beyond the bounds of the law to resist and address oppressive systems of power which Western conceptions of liberation and emancipation fail to do.